2015
DOI: 10.1007/s12221-015-1119-1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and thermal properties of epoxy composites reinforced with waste peanut shell powder as a bio-filler

Abstract: Bio-filled polymer composites are gradually replacing plastics to achieve the aim of environmental sustainability. Present study has been carried out to prepare the composites made by reinforcing waste peanut shell powder (PSP) as a natural filler into epoxy resin matrix. The natural filler extracted by manual process was subjected to alkali treatment with the concentrations of 2, 5 and 7 w/v%. The composites fabricated by varying the weight fractions of filler in the range of 5 to 15 wt%. The effects of bio-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(46 citation statements)
references
References 23 publications
0
41
0
Order By: Relevance
“…Zaaba et al 25 showed the positive effect of previous chemical modification of peanut shell with poly(vinyl alcohol)-PVA to improve overall properties of recycled polypropylene (PP). Prabhakar et al 26 analyzed the effect of peanut shell fillers (without and with a previous alkaline treatment) in epoxy thermosetting resins. In addition, the potential of peanut shell as base material for particle board manufacturing was studied, 27,28 but its use is not generalized.…”
Section: Introductionmentioning
confidence: 99%
“…Zaaba et al 25 showed the positive effect of previous chemical modification of peanut shell with poly(vinyl alcohol)-PVA to improve overall properties of recycled polypropylene (PP). Prabhakar et al 26 analyzed the effect of peanut shell fillers (without and with a previous alkaline treatment) in epoxy thermosetting resins. In addition, the potential of peanut shell as base material for particle board manufacturing was studied, 27,28 but its use is not generalized.…”
Section: Introductionmentioning
confidence: 99%
“…So, PS/ ZnO was selected as the best catalyst for the model reaction. The catalyst loading and heating conditions were also optimized (entry 13,17,18). As a result, the optimum conditions obtained were the use of 20 mg of PS/ZnO under microwave irradiation and a reaction time of 2 min.…”
Section: Resultsmentioning
confidence: 99%
“…Every year around 13.7 million tons of PS are discarded in the environment or burned (2)(3)(4). In contrast limited value-added uses exist for their removal among which we can mention the preparation of solid acid catalyst for biodiesel production and etherification of glycerol (5)(6)(7), natural dye and metal absorbents (8)(9)(10)(11)(12)(13)(14), biofilter based on their mechanical and thermal properties (15)(16)(17), and they are also used in the production of cellulose (18). PS are mainly composed of three biopolymers: lignin, cellulose and hemicellulose.…”
Section: Introductionmentioning
confidence: 99%
“…End joint with bonded nature are better than the bolted end joints for stress concentration and delamination [15]. Groundnut shell powder is used for composite and tested for thermal and mechanical properties, which shows good result with 15 wt% composition [17]. Treatment performed on jute fiber has shown better creep behaviour than untreated fiber composite [19].…”
Section: Literature Reviewmentioning
confidence: 99%